Managerial competencies critical for enhancing organisational responsiveness and agility in digital transformation of SMEs: A qualitative study - Philipp Boateng; Cecília Olexová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
This research aims to identify and categorise the key competencies required for managers to effectively lead small and medium-sized enterprises (SMEs) through the digital transformation process. Utilising a qualitative approach, the study employs Mayring's content analysis to examine semi-structured interviews with ten SME representatives in Germany. The findings reveal that agile leadership, and the integration of innovative technologies are crucial for enhancing organisational responsiveness and agility. However, significant gaps in standardising systems and processes remain a challenge. The study underscores the importance of adaptive leadership, and the strategic use of digital tools to foster a resilient organisational culture. The insights provided contribute to the broader understanding of how SMEs can effectively implement digital transformation, highlighting the need for specialised leadership competencies to drive this change. The significance of the study lies in its potential to guide SME managers and policymakers in developing strategies that support sustainable digital growth and innovation.
Keywords: M1; M5; O15; J24; 330; Digital Transformation; SMEs; Qualitative Content Analysis; Mayring; Agile Leadership; Empowerment; Teams